BDNF-Dependent Effects on Amygdala–Cortical Circuitry and Depression Risk in Children and Youth. (6th April 2017) - Wheeler, Anne L; Felsky, Daniel; Viviano, Joseph D; Stojanovski, Sonja; Ameis, Stephanie H; Szatmari, Peter; Lerch, Jason P; Chakravarty, M Mallar; Voineskos, Aristotle N
Abstract: The brain-derived neurotrophic factor (BDNF) is critical for brain development, and the functional BDNF Val66Met polymorphism is implicated in risk for mood disorders. The objective of this study was to determine how the Val66Met polymorphism influences amygdala–cortical connectivity during neurodevelopment and assess the relevance for mood disorders. Age- and sex-specific effects of the BDNF Val66Met polymorphism on amygdala–cortical connectivity were assessed by examining covariance of amygdala volumes with thickness throughout the cortex in a sample of Caucasian youths ages 8–22 that were part of the Philadelphia Neurodevelopmental Cohort ( n = 339). Follow-up analyses assessed corresponding BDNF genotype effects on resting-state functional connectivity ( n = 186) and the association between BDNF genotype and major depressive disorder (MDD) ( n = 2749). In adolescents, amygdala–cortical covariance was significantly stronger in Met allele carriers compared with Val/Val homozygotes in amygdala–cortical networks implicated in depression; these differences were driven by females. In follow-up analyses, the Met allele was also associated with stronger resting-state functional connectivity in adolescents and increased likelihood of MDD in adolescent females. The BDNF Val66Met polymorphism may confer risk for mood disorders in females through effects on amygdala–cortical connectivity during adolescence, coinciding with a period in the lifespan when onset of depression often occurs, more commonly in females.